Mental Health and Wellness of Service Providers Working with People Experiencing Homelessness in Canada: A National Survey from the Second Wave of the COVID-19 Pandemic. (May 2022) - Kerman, Nick; Ecker, John; Gaetz, Stephen; Tiderington, Emmy; A. Kidd, Sean
Objective: This study examined the scope of common mental health problems and perceived impacts of the COVID-19 pandemic among direct service providers working with people experiencing homelessness in Canada. Method: This cross-sectional study used an online survey that was disseminated to homeless service, supportive housing, and harm reduction organizations and networks. Data were collected on depression, anxiety, stress, post-traumatic stress, compassion satisfaction and fatigue, and substance use problems as well as pandemic-related changes in mental health and wellness. A total of 701 service providers completed the survey and were included in data analysis. Descriptive statistics were used to examine the primary research questions, with hierarchical multiple regression models also being fit to explore mental health and wellness differences by occupational service setting. Results: Most direct service providers (79.5%) working with people experiencing homelessness reported a decline in their mental health during the pandemic. There were high rates of common mental health problems within the sample that are largely consistent with those found among health-care workers during the pandemic. Occupational service settings were not associated with the severity of mental health problems, indicating pervasive issues across the workforce, though providers who were younger and spent more time in direct service roles were at greater risk. Conclusions: The common mental health problems and negative impacts of the pandemic among service providers working with people experiencing homelessness highlight a highly vulnerable workforce that could benefit from improved access to supports. Given the similarities between our findings and other studies examining essential workforces, it is recommended that initiatives that provide accessible mental health care to the health-care workforce during the pandemic be expanded to include homeless and social service providers.